Social Interaction in Basic Training for Prospective Civil Servants Using the Blended Learning Method - Marantika, Jerry; Frinaldi, Aldri (Jurnal Ilmiah Ekotrans & Erudisi, 2023)
The movement in the style of Basic Training for Civil Servant Candidates (CPNS) from traditional or face-to-face methods to blended learning has been prompted by advancements in information technology and the COVID-19 pandemic outbreak. Changes in training patterns result in alterations to the social interaction processes conducted among organizers, teachers, and participants. In the classical method, direct social contact is abundant, whereas in blended learning, digital-based communication media predominantly facilitate the engagement process. This study employs a literature review methodology to offer a comprehensive picture of social interactions during the CPNS Basic Training process, utilizing the blended learning approach.